2021
DOI: 10.1016/j.xcrm.2021.100398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Faecalibacterium prausnitzii strains for gut microbiome-based intervention in Alzheimer’s-type dementia

Abstract: Evidence linking the gut-brain axis to Alzheimer's disease (AD) is accumulating, but the characteristics of causally important microbes are poorly understood. We perform a fecal microbiome analysis in healthy subjects and those with mild cognitive impairment (MCI) and AD. We find that Faecalibacterium prausnitzii (F. prausnitzii) correlates with cognitive scores and decreases in the MCI group compared with the healthy group. Two isolated strains from the healthy group, live Fp360 and pasteurized Fp14, improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 83 publications
3
57
0
Order By: Relevance
“…Five cross-sectional studies of differences in gut microbiota between patients with AD and controls found that several microbes were less abundant in AD, including Faecalibacterium prausnitzii, Eubacterium , Anaerostipes , Ruminococcus , and Roseburia spp, while other microbes, such as Odoribacter splanchicus , Bacteroides, Prevotella , and Alistipes spp., were more abundant ( 16 20 ). In line with these studies, we found that many of the highest ranked predictors for amyloid and p-tau status belonged to the Lachnospiraceae family, including Roseburia hominis , [Ruminococcus] torques, Lachnoclostridium, Monoglobus and Marvinbryantia spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Five cross-sectional studies of differences in gut microbiota between patients with AD and controls found that several microbes were less abundant in AD, including Faecalibacterium prausnitzii, Eubacterium , Anaerostipes , Ruminococcus , and Roseburia spp, while other microbes, such as Odoribacter splanchicus , Bacteroides, Prevotella , and Alistipes spp., were more abundant ( 16 20 ). In line with these studies, we found that many of the highest ranked predictors for amyloid and p-tau status belonged to the Lachnospiraceae family, including Roseburia hominis , [Ruminococcus] torques, Lachnoclostridium, Monoglobus and Marvinbryantia spp.…”
Section: Discussionmentioning
confidence: 99%
“…We included 170 patients from the Amsterdam Dementia Cohort, comprising 33 with AD dementia (66 ± 8 years, 46%F, mini-mental state examination (MMSE) 21 [19][20][21][22][23][24]), 21 with MCI (64 ± 8 years, 43%F,) and 116 with SCD (62 ± 8 years, 44%F, MMSE 29 [28][29][30]). Fecal samples were collected and gut microbiome composition was determined using 16S rRNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, integrative multiomics analysis was performed on proteins and metabolites, to identify the biological mechanism involved in the selective digestion of inulin in the intestine by F. prausnitzii. To investigate molecular-level cellular metabolic changes using multiomics approaches, we used F. prausnitzii strain A2-165, whose complete genome sequence has already been well reported (Miquel et al, 2013;Fitzgerald et al, 2018;Ueda et al, 2021). First, to confirm the preference for dietary carbohydrates in F. prausnitzii, we compared the growth of the bacterium in the presence of several carbon sources and confirmed significant growth in inulin.…”
Section: Introductionmentioning
confidence: 99%